Immunosuppressive agents in the treatment of chronic idiopathic thrombocytopenic purpura' - A. H. Markum; Maria Abdulsalam; S. Muslichan; Iskandar W. (Indonesian Pediatric Society, 1973)
Acute idiopathic thrombocytopenic purpura (I. T.P.) in childhood is acondition with a self-limiting course that will usually improve spontaneously. In severe cases, however, blood transfusion and corticosteroids are indicated. Lusher and Zuelzer (1966) who analysed 152 cases of acute I.T.P. in children concluded that 92.6% of the untreated as well as 97.5% of the corticosteroid-treated gave uneventful recovery without recurrence of thrombocytopenia. On the other hand, in chronic I.T.P., where the immune mechanisms playa more important role than in acute I.T.P., administration of corticosteroids seems of little value. Harrington et al. (1951) found the presence of platelet antibodies in 8 out of 10 cases of chronic I.T.P. The importance of platelet antibodies which either destroy or inhibit platelet formation from megakaryocytes in the bone marrow; has been demonstrated by other investigators (Kuramoto, 1966; Rolovic et aI., 1970).